Development of similarity module based on ethnomathematics of Troso Jepara fabric motifs to improve numeracy literacy - Dina Noviyanti; Mochamad Abdul Basir (UNION : Jurnal Ilmiah Pendidikan Matematika, 2025)
This study aims to develop a similarity learning module based on ethnomathematics by raising the Troso Jepara fabric motif as a relevant local cultural context, and to examine the validity and practicality of the module in improving students' numeracy literacy. The ethnomathematics approach is used to integrate cultural values ​​in mathematics learning, so that students not only understand the concept of similarity abstractly but are also able to relate it to everyday life. The research method used is the 4D development model (Define, Design, Develop, Disseminate), with a focus on the development and validation stages. For the Disseminate stage, this stage was not carried out. The instruments used include expert validation sheets and teacher and student response questionnaires. The results of the validation by experts obtained an average final score of 3.62, indicating that the module is in the very valid category with several suggestions for product revision, while the results of teacher and student responses obtained an average score of 3.36 indicating that the module is practical to use. Thus, this module can be an alternative contextual and meaningful teaching material in mathematics learning at junior high school level. The results of this study indicate that the developed learning module has met the criteria of being valid and practical for use. Through this study, teachers can integrate local cultural values ​​into mathematics learning, which not only enriches the ethnomathematics approach but also supports the improvement of students' numeracy literacy. This module has a positive impact on students' ability to understand the concept of similarity and apply it relevantly in the context of local culture, so that learning becomes more meaningful and applicable.